UJI EFEKTIVITAS LARUTAN MADU SEBAGAI ANTIBAKTERI TERHADAP PERTUMBUHAN Staphylococcus aureus DAN Pseudomonas aeruginosae DENGAN METODE DISK DIFFUSION - Yuliati Yuliati (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2017)
Honey is one of the traditional medicine that can be used in the community for wound treatment since centuries ago. Honey has an antibacterial effect, due to its high osmolarity , hydrogen peroxide content, low pH and low activity. The pH of honey is acidic (ranges about 3.2-4.5), inhibits the metabolism of Gram negative and positive bacteria, in consequence would be bacterial metabolism inhibition. This condition would lead to bacterial lysis. Honey can be used as wound treatment, controls blood sugar in diabetes patient`s, antioxidants, prevents inflammation outer layer surrounding the mouth of the laser beam treatment of cancer patients, treats gastrointestinal inflammation, as well as the material beauty products, hair and skin. This study was conducted to determine the comparative effectiveness of honey solution on the growth of Staphylococcus aureus and Pseudomonas aeruginosae with various concentrations of 105 ppm, 106 ppm , 5x106 ppm , 107 ppm , and 108 ppm by well diffusion method. According to the MIC result on S .aureus, its is included in weak category, with an average diameter 6.5 mm , 10.5 mm, 12 mm, and 14.7 mm on 106 ppm, 5x106 ppm, 107 ppm, and 108 ppm, respectively. Based on the MIC result on Pseudomonas aeruginosae, it also included in weak category, with an average diameter 6 mm , 8.5 um , 9.5 mm, 10.5 mm on 106 ppm, 5x106 ppm on 106 ppm, 5x106 ppm, 107 ppm, and 108 ppm, respectively. This study concluded that antibacterial from honey solution is more effective against Staphylococcus aureus than Pseudomonas aeruginosae, although there are no significantly difference.